Reduction patterns of Japanese encephalitis incidence following vaccine introduction into long-term expanded program on immunization in Yunnan Province, China - Xiao-Ting Hu; Qiong-Fen Li; Chao Ma; Zhi-Xian Zhao; Li-Fang He; Ting-Ting Tang; Wen Yu; Philip Owiti (BMC, 2019)
Abstract Background Japanese encephalitis (JE) is a leading cause of childhood viral encephalitis both at global level and in China. Vaccination is recommended as a key strategy to control JE. In China most JE cases have been reported in southwest provinces, which include Yunnan. In this study, we quantify the epidemiological shift of JE in Yunnan Province from 2005 to 2017, covering before and after the introduction of JE vaccination into routine Expanded Program on Immunization (EPI) in 2007. Methods We used routinely collected data in the case-based JE surveillance system from 2005 through 2017 in Yunnan. Cases were reported from hospital and county-level Centers for Disease Control in line with the National JE Surveillance Guideline. Epidemiological data were extracted, analysed and presented in appropriate ways. Immunization coverage was estimated from actual JE doses administered and new births for each year. Results A total 4780 JE cases (3077 laboratory-confirmed, 1266 clinical and 437 suspected) were reported in the study period. Incidence of JE (per 100 000 population) increased from 0.95 in 2005 to 1.69 in 2007. With increase in vaccination coverage, incidence rates decreased steadily from 1.16 in 2009 to 0.17 in 2017. However, seasonality remained similar across the years, peaking in June-September. Banna (bordering Myanmar and Laos), Dehong (bordering Myanmar), and Zhaotong (an inland prefecture) had the highest incidence rates of 2.3, 1.9, and 1.6, respectively. 97% of all cases were among local residents. As vaccination coverage increased (and incidence decreased), proportion of JE cases among children < 10 years old decreased from 70% in 2005 to 32% in 2017, while that among adults ≥20 years old increased from 12 to 48%. There were a large number of JE cases with unknown treatment outcomes, especially in the earlier years of the surveillance system. Conclusions The 13-year JE surveillance data in Yunnan Province showed dramatic decrease of total incidence and a shift from children to adults. Improving vaccination coverage, including access to adults at risk, and strengthening the JE surveillance system is needed to further control or eliminate JE in the province.